Analisis Nilai-Nilai Kepemimpinan Profetik dalam Program Kamus Biru di SMP Negeri 25 Padang - sukma ramadhani; Halomoan Halomoan (Journal of Innovative and Creativity, 2026)
Prophetic leadership is a leadership model that emulates the prophetic traits of Prophet Muhammad SAW, highly relevant for character education programs in Islamic schools. The Kamus Biru (Kajian Muslimah Berkarakter, Inovasi, Religius, dan Update) program at SMP Negeri 25 Padang serves as a strategic vehicle to instill these values in female students. This study employs a qualitative method with a case study approach, conducted at SMP Negeri 25 Padang. Informants included the Vice Principal for Curriculum, the Kamus Biru Program Advisor, program administrators, and student participants. Data were collected through observation, in-depth interviews, and documentation, then analyzed using the Miles, Huberman, and Saldana interactive model. The results indicate that: (1) The prophetic leadership values in the Kamus Biru program encompass three main pillars humanization, liberation, and transcendence and four prophetic traits: siddiq (honesty), amanah (trustworthiness), tabligh (communicativeness), and fathanah (intelligence). (2) These values are realized through students' active involvement as the primary actors (humanization), positive behavior guidance (liberation), and strengthening of spiritual awareness (transcendence). Honesty is enforced through an attendance system (siddiq), responsibility according to organizational structure (amanah), effective information delivery (tabligh), and creativity in designing relevant activities (fathanah). (3) Supporting factors include active teacher mentoring and available facilities, while inhibiting factors are limited time due to students' dense schedules and shared room usage.